2018
DOI: 10.1002/nau.23491
|View full text |Cite
|
Sign up to set email alerts
|

Urotherapy in children with dysfunctional voiding and the responsiveness of two condition‐specific questionnaires

Abstract: Aims We sought to establish the responsiveness of the Dutch Vancouver Symptom Score for Dysfunctional Elimination Syndrome (VSSDES) and Pediatric urinary incontinence Quality of life (PinQ) questionnaires. Secondary, we evaluated the outcome of urotherapy extended for children with dysfunctional voiding (DV). Methods This cross‐sectional multicenter study was done in one tertiary and two community hospitals. Children with DV were included, also when refractory to previous urotherapeutic treatment. The question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…11 A recent study by Noordhoof et al found that the VSS was not effective in discriminating between patients who had a clinically significant response to extended urotherapy with biofeedback and those who did not. 12 In our study, we found that both "responders" and "nonresponders" demonstrated statistically significant improvements in symptom scores following at least two sessions of PFBT. The "responders" had an average decrease of nine points (P = <0.0001), a 47% decrease.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…11 A recent study by Noordhoof et al found that the VSS was not effective in discriminating between patients who had a clinically significant response to extended urotherapy with biofeedback and those who did not. 12 In our study, we found that both "responders" and "nonresponders" demonstrated statistically significant improvements in symptom scores following at least two sessions of PFBT. The "responders" had an average decrease of nine points (P = <0.0001), a 47% decrease.…”
Section: Discussionmentioning
confidence: 47%
“…PFBT "Responders" were defined as patients demonstrating a change in pelvic floor EMG activity from inappropriately active during the voiding phase pre-PFBT to appropriately quiet during voiding following PFBT therapy. We analyzed symptom score questionnaires only if questions (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) were answered with an appropriate single answer. The primary outcome measures were quiescence of pelvic floor EMG activity and change in symptom scores over time.…”
Section: Methodsmentioning
confidence: 99%
“…Of these, 27 had a complete and 14 a partial response. 29 In a retrospective analysis of 61 patients, 65.5% showed a significant improvement for DV and daytime UI through a biofeedback treatment. 30 Pharmacotherapy is not recommended for DV itself by the ICCS, 20 but can play an ancillary role for comorbid conditions such as OAB.…”
Section: In Childhoodmentioning
confidence: 99%
“…In a recent study of 64 children with DV, 56 underwent extended urotherapy with a median duration of treatment of 18 weeks. Of these, 27 had a complete and 14 a partial response . In a retrospective analysis of 61 patients, 65.5% showed a significant improvement for DV and daytime UI through a biofeedback treatment .…”
Section: Current Management Of DV In Childhoodmentioning
confidence: 99%
“…The interprofessional approach for the treatment of PDFs was primarily introduced by pediatricians [12], whose clinical activities were supported by urotherapists treating children with urinary and fecal incontinence [13,14]. A review addressing urotherapy in children revealed that the urotherapist contributed to a reduced urinary and fecal incontinence [13].…”
Section: Introductionmentioning
confidence: 99%